Evaluation of Development of Nonalcoholic Fatty Pancreas Disease After Post-Endoscopic Retrograde Cholangiop ancreatography Pancreatitis in Liver Transplant Patients: Computerized Tomography Versus Ultrasound - Nuransoy Cengiz, Ayşe; Bilgiç, Yılmaz; Karatoprak, Sinan; Gökçe, Ayşe; Evren, Bahri; Akbulut, Ahmet Sami; Yılmaz, Sezai (Turkish Journal of Gastroenterology, 2023)
Background/Aims: Post-endoscopic retrograde cholangiopancreatography pancreatitis (PEP) is the most common serious adverse event in liver transplant patients The average incidence has been reported as 1.3%-15.1% in prospective series. In our study, we have prospectively evaluated the prevalence of nonalcoholic fatty pancreatic disease (NAFPD) after PEP via computerized tomography (CT) and determined the ratio of fatty pancreas by ultrasound imaging in liver transplant patients. Materials and Methods: We have retrospectively analyzed 2922 patient files, and 146 patients were indicated for ERCP. PEP was observed in 32 patients. After presenting the significant association between the NAFPD and PEP, we prospectively reached 32 patients included in the study. Ten out of those patients have been performed ultrasound with regard to NAFPD. Results: PEP was defined in 32 patients in whom CT was performed to investigate NAFPD. When the patients were contacted, it was observed that 12% were deceased, 71% were alive, but 15% of them were untraceable. Ultrasound has been performed on 10 of 32 patients to determine NAFPD. There was a significant reduction in post-PEP pancreas/spleen rate compared to pre-PEP pancreas/ spleen rate (P = .001). Both the pre-PEP and post-PEP pancreas-spleen difference dropped significantly (P = .002). Conclusion: Ultrasound imaging could be utilized as a scanning test and an alternative to evaluate and diagnose NAFPD, particularly in risky patients.